Educational Innovation for Leaders of Private Islamic Religious Universities - Mahdayeni, Mahdayeni; Mutalib, Abdul; Hawasyi, Luqmanul Hakim; Aprianto, Iwan; Hariandi, Ahmad (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research aims to analyze educational innovations carried out by leaders at Private Islamic Universities in Jambi Province. Using a descriptive qualitative approach with case studies at two institutes in Jambi Province, this research involved observation, interviews, and documentation as data collection techniques. Research locations include the Yasni Muaro Bungo Islamic Institute and the Tebo Islamic Institute. Research subjects included the IAI Chancellor, lecturers, and staff. The research results show that higher education leaders in Jambi Province have innovated in Islamic religious education through several leadership patterns. They optimize the internal and external potential of the campus, implement superior strategies for lecturers and students, and activate communication between campus leaders and employees. Obstacles include limited human resources, inadequate facilities, and an insufficient budget to support quality lecture activities. To overcome these obstacles, the Leadership has established a systematic work structure, explained job descriptions clearly, carried out collaboration and comparative studies with academic and government institutions, both private and state, and designed a qualification-based national curriculum. They also provide opportunities for lecturers to continue their education to the doctoral level and participate in certification programs, training and research seminars, and community service. Recommendations include competent support, management improvements, and adaptive leadership development. Government support and the development of quality and adaptive Leadership are also recommended.